A inclusão do aluno com transtornos funcionais específicos: uma análise a partir de um estado da arte - PEREIRA, Sâmeque Albuquerque de Sousa (2024)
The aim of this study was to analyze theoretical productions on the inclusion of students whit specific functional disorders in mainstream schools, as well as to identify and analyze what has been produced and discussed in these theoretical productions. To this end, the State of the Art research was used as the data collection method, Based on the information obtained through the data analysis, it can be seen that specific functional disorders are still a new topic due to the many discussions, but their understanding is of great importance for guaranteeing the education of this target public. Through the study carried out, it was possible to perceive a certain invisibility of this public with regard to guaranteeing the right to education, which requires greater investment in the education of these individuals.